PERTENTANGAN NILAI AKHLAK ISLAM DALAM NOVEL TIVI MENURUT AL-GHAZALI - Muhammad Apandi, Siti Nur Anis Binti; Tengku Mohd Ali, Tengku Intan Marlina Binti; Mat Hussien, Eizah Binti; Mohd Balwi, Mohd Taufik Arridzo Bin (JURNAL MELAYU SEDUNIA, 2020)
Shahnon Ahmad, the second Malaysian National Laureate has produced many works of art which raised various issues related to the national crisis from the economic, political and, social point of view among the community and the government. The TIVI novel produced in 1995 has highlighted the issues of moral decay in a family living in a village. The issues of morality dealt through various characters that violates Islamic teaching and the Malay norms. Moral crisis includes immoral behaviour and actions, homosexuality, promiscuity and the collapse of family institutions. The study was conducted to comprehend the factors of moral crisis which is contrary to the Islamic teaching. The study also uses Bidayatul-Hidayah approaches, which was introduced by Imam Al-Ghazali. It used the perspective of the Qur’an and hadith. This study has three main objectives, namely, to identify the issues of moral decay portrayed in the TIVI novel, to analyze and evaluate the impact of moral decay in the novel using the Islamic approach. This objective was set under the premise on the effect of technology abuse which has resulted in the conflict of Islamic moral values in the Muslim’s community. The methodology used was a qualitative study which involves careful reading and interpretation of written materials as supporting data. The findings concluded that the issues of moral decay shown in the TIVI novel is entirely wrong based on the Islamic perspective and should be avoided so that people can live in harmony in the setting of family institution as well as social institutions.